β-TrCP Restricts Lipopolysaccharide (LPS)-Induced Activation of TRAF6-IKK Pathway Upstream of IκBα Signaling - Liu, Jin; Yuan, Yukang; Xu, Jing; Xiao, Kui; Xu, Ying; Guo, Tingting; Zhang, Liting; Wang, Jun; Zheng, Hui (Frontiers in Immunology, 2018)
β transducin repeat-containing protein (β-TrCP) is a Skp1-Cul1-F-box ubiquitin ligase, which plays important roles in controlling numerous signaling pathways. Notably, β-TrCP induces ubiquitination and degradation of inhibitor of NF-κB (IκBα), thus triggering activation of NF-κB signaling. Here, we unexpectedly find that β-TrCP restricts TRAF6-IKK signaling upstream of IκBα induced by lipopolysaccharide (LPS). In LPS-Toll-like receptor 4 (TLR4) pathway, protein kinase D1 (PKD1) is essential for activation of TRAF6-IKK-IκBα signaling including TRAF6 ubiquitination, IKK phosphorylation and subsequent IκBα degradation. We found that LPS promotes binding of β-TrCP to PKD1, and results in downregulation of PKD1 and recovery of IκBα protein level. Knockdown of β-TrCP blocks LPS-induced downregulation of PKD1. Supplement of enough PKD1 in cells inhibits recovery of IκBα protein levels during LPS stimulation. Furthermore, we demonstrate that β-TrCP inhibits LPS-induced TRAF6 ubiquitination and IKK phosphorylation. Taken together, our findings identify β-TrCP as an important negative regulator for upstream signaling of IκBα in LPS pathway, and therefore renew the understanding of the roles of β-TrCP in regulating TLRs inflammatory signaling.